Effects of variation status and enzyme activity for UDP-glucuronosyltransferase 1A1 gene on neonatal hyperbilirubinemia - May-Jen Huang; Yu-Cheng Lin; Kevin Liu; Pi-Feng Chang; Ching-Shan Huang (Pediatrics and Neonatology)
Background: We found that Taiwanese adults carrying genotypes of UDP-glucuronosyltransferase (UGT) 1A1 with enzyme activity ≤40% of normal were at high risk for developing Gilbert's syndrome. However, the relationship between UGT1A1 activity and neonatal hyperbilirubinemia has never been evaluated for Taiwanese. Methods: We enrolled 141 hyperbilirubinemic neonates partially fed supplementary infant formula and 432 controls; and 112 hyperbilirubinemic neonates exclusively breastfed and 493 controls. The five single nucleotide polymorphisms (SNPs) at nucleotides −53, 211, 686, 1091 and 1456 in the UGT1A1 gene were determined and UGT1A1 activity was estimated. Odds ratios (ORs) of variation status in the UGT1A1 gene and enzyme activity for the development of neonatal hyperbilirubinemia were calculated, respectively. Results: For neonates partially fed supplementary infant formula, the adjusted OR (AOR) for the development of hyperbilirubinemia was significantly higher in the neonates carrying the homozygous variation (211AA) in the UGT1A1 gene than for those carrying the wild type (AOR = 6.00, p < 0.001). Only the AOR of those carrying UGT1A1 activity ranked 31–40% of normal was statistically significant (AOR = 3.16, p < 0.001). For the hyperbilirubinemic neonates exclusively breastfed, AOR for the development of hyperbilirubinemia is positively correlated to degree of variation (AOR = 1.95, 2.19 and 4.53; with p = 0.003, 0.05 and < 0.001, respectively), while the effect of UGT1A1 enzyme activity was varied (AOR = 1.02–3.72, with p = 0.95∼<0.001). Conclusion: The estimated enzyme activity depending on combination of SNPs (genotypes) in the UGT1A1 gene could not be utilized to explain the development of neonatal hyperbilirubinemia. We reconfirm that the −53 A(TA)7TAA/A(TA)7TAA is not, while the 211AA is a risk factor for the development of neonatal hyperbilirubinemia in Taiwanese.